Anti-cancer activity and immunoadjuvant properties of edible bird’s nest extracts on human breast cancer cell line - M. Yoshiny S. Maruthai, 1991-, author 625475; Lee, Ting Hun, 1972-, supervisor 508999; Chua, Kien Hui, supervisor 512656; Haslinda Abd. Kadir, supervisor 372573; Fakulti Kejuruteraan. Sekolah Kejuruteraan Kimia dan Kejuruteraan Tenaga 619081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Falsafah) - Universiti Teknologi Malaysia, 2019